Whole-of-Society Peacebuilding - Martin, Mary; Bojicic-Dzelilovic, Vesna (Taylor & Francis, 2019)
The complex problems of peace, security, and development in societies affected by conflict increasingly demand innovative ideas, and comprehensive strategies to tackle the diverse, simultaneous, and daunting challenges faced in trying to rebuild states and communities after war. This comprehensive collection sets out a 'Whole-of-Society' (WoS) approach which focuses on the social contexts within which conflict resolution and prevention take place. The aim of WoS is to grasp the complexity both within local society and in the relations between external peacebuilders and the people they set out to help. The book argues that, by understanding multiple actors, their relationships, and the conditions in which they operate, complexity becomes an opportunity to be grasped, not simply an impediment to building peace. This volume offers a novel perspective to advance and enrich debates on ownership of peace processes, resilience, hybridity, and liberal peacebuilding, and how these are influenced by local agency and social dynamics. Drawing on examples of conflicts in Ukraine, Mali, Yemen, Sri Lanka, Kosovo, and Georgia, the authors seek to address the operational gaps between interventions designed by outsiders, and outcomes on the ground, suggesting how policymakers and civil society activists can achieve better configurations of external and local resources, delegate initiatives, and empower conflicted societies. This book was originally published as a special issue of the journal Peacebuilding. Chapter 6 is available Open Access at https://www.routledge.com/products/9780367236885.